A phthalocyanine-grafted MA–VA framework polymer as a high performance anode material for lithium/sodium-ion batteries. Issue 28 (1st July 2021) - Zhao, Jianjun; Xu, Yong; Chen, Jun; Tao, Lihong; Ou, Caixia; Lv, Weixia; Zhong, Shengwen
Abstract : A nickel phthalocyanine-grafted MA–VA polymer as a high-performance anode material for lithium/sodium-ion batteries. Abstract : A porous MA–VA–PcNi polymer was prepared by grafting nickel phthalocyanine (PcNi) onto the main chain of a maleic anhydride–vinyl acetate (MA–VA) polymer, and an MA–VA–PcNi electrode is prepared by electrospinning technology to inhibit the agglomeration of the active powder effectively, which produces spherical particles with a diameter of 100–300 nm. The synthesized MA–VA–PcNi polymer is used as the anode for lithium-ion and sodium-ion batteries, exhibiting excellent energy storage behaviors. The MA–VA–PcNi/Li battery displays a high capacity of 610 mA h g −1 and can still remain at 507 mA h g −1 with a retention rate of 83.1% after 400 cycles at a current density of 200 mA g −1 . Even at a high current density of 2 A g −1, the specific capacity can remain at 195 mA h g −1 . In addition, the MA–VA–PcNi/Na battery displays a high capacity of 336 mA h g −1 and can still remain at 278 mA h g −1 with a retention rate of 82.7% after 400 cycles at a current density of 100 mA g −1 . A high specific capacity of 164 mA h g −1 can also be achieved at a high current density of 1 A g −1 . After nickel phthalocyanine (PcNi) was grafted onto the MA–VA polymer, aggregation between phthalocyanine rings was effectively prevented, and this exposes more active sites. At the same time, the spherical particles obtained by electrospinning technology further improve the dispersion and increase the number of active sites of the active materials. Finally, the electrode materials show excellent energy storage behavior for lithium-ion and sodium-ion batteries, which provides a new idea for designing high-performance energy storage materials for organic electrodes.